The Effect of Financial Factors on Firm Value in the Food and Beverage Subsector Listed on the Indonesia Stock Exchange - Roza Fitriawati (Jurnal Multidisiplin Sahombu, 2026)
This study examines the effect of financial factors on firm value in companies operating within the food and beverage subsector listed on the Indonesia Stock Exchange. Firm value reflects market perceptions of a company’s performance and long term prospects, making it a critical indicator for investors and stakeholders. Financial factors analyzed in this study include capital structure, profitability, liquidity, and firm size, which are commonly used to assess corporate financial health. The research employs a quantitative approach using secondary data obtained from published annual reports and financial statements. Empirical analysis is conducted to evaluate both the direction and significance of the relationships between financial factors and firm value. The findings indicate that profitability has a positive and significant influence on firm value, suggesting that companies with stronger profit generating capabilities are more highly valued by the market. In contrast, capital structure, liquidity, and firm size do not show a significant effect on firm value. These results imply that investors in the food and beverage subsector place greater emphasis on profitability than on other financial indicators when forming valuation judgments.